THE GABION HOUSE REVISITED - Regan Potangaroa (Journal of Architecture&ENVIRONMENT, 2013)
Most material on a “Green Concept” for addressing the environmental, social, cultural and institutional issues resulting from global warming and climate change through the implementation of architecture and environmental design usually starts with the “big” picture, policy/theoretical statement. And then migrates towards the “specific design” criteria. However, there is a problem with this approach and experience questions whether it adequately or often appropriately connects with practice as it migrates?The paper revisits a community in Port au Prince Haiti that received gabion houses constructed as part of the response to the 12 January 2010 earthquake. The gabion house was perceived within the humanitarian shelter community as an excellent green concept because it reused rubble, could be built using local skills and was economical comparable to other options. Thus, the question posed to the community after nearly 2 years of living in these gabion houses was whether the houses were more effective than the “standard” house? And from that reflective process are taken design tips for possibly a more humane and Greener Concept.